GRAMMATICAL ERRORS IN THESIS ABSTRACT OF INDUSTRIAL ENGINEERING DEPARTMENT STUDENTS OF UNIVERSITAS SUMATERA UTARA - Anggi Ridho Habibi; Zuindra Zuindra (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
GRAMMATICAL ERRORS IN THESIS ABSTRACT OF INDUSTRIAL ENGINEERINGDEPARTMENT STUDENTS OF UNIVERSITAS SUMATERA UTARAAnggi Ridho Habibi1, Zuindra2Universitas Harapan MedanJl. HM. Joni No.70 C, Teladan Bar., Kec. Medan Kota, Kota Medan, Sumatera Utara, 20216, IndonesiaEmail: anggiridhohabibi@gmail.com, zuindraidris@gmail.comAbstractThis research focused on the grammatical errors found in the undergraduate thesis abstracts ofIndustrial Engineering Department Students of Universitas Sumatera Utara. There are three problemsand objectives formulated in this study that focused on finding out the types, process of analyzing, andthe most dominant type of grammatical error occurred in the thesis abstract. This research is adescriptive qualitative study that examined the thesis abstracts using the steps of error analysisproposed by Ellis and Barkhuizen (2005). The grammatical errors are classified into the 4 types ofgrammatical errors proposed by Dulay, Burt, and Krashen (1982), which are addition, omission,misformation, and misordering. The results showed that there were 143 errors found from the 24 thesisabstracts that being sampled. Omission is the most dominant type of grammatical error with 67 errors(47%), followed by misformation with 35 errors (25%), addition with 29 errors (20%), and misorderingwith 12 errors (8%).Keywords: grammar, types, error, error analysis, abstract